Genetic Diversity And Forensic Statistical Support For The 12 X-str Markers In The Malaysian Indian Population Using Qiagen Investigator® Argus X-12 Qs Kit - Aedrianee Reeza Alwi; Naji Arafat Mahat; Faezah Mohd Salleh; Seri Mirianti Ishar; Mohammad Rahim Kamaluddin; Mohd Radzniwan A Rashid; Sharifah Nany Rahayu Karmilla Syed Hassan (ScienceDirect, 2024)
Indexed by WOS/Scopus/ERA